AdTurtle: An advanced Turtle trading system - Dimitrios Vezeris; Ioannis Karkanis; Themistoklis Kyrgos (Journal of Risk and Financial Management, 2019)
For this research, we implemented a trading system based on the Turtle rules and examined its efficiency when trading selected assets from the Forex, Metals, Commodities, Energy and Cryptocurrency Markets using historical data. Afterwards, we enhanced our Turtle-based trading system with additional conditions for opening a new position. Specifically, we added an exclusion zone based on the ATR indicator, in order to have controlled conditions for opening a new position after a stop loss signal was triggered. Thus, AdTurtle was developed, a Turtle trading system with advanced algorithms of opening and closing positions. To the best of our knowledge, for the first time this variation of the Turtle trading system has been developed and examined.
Keywords: 330; algorithmic trading; Stop Loss; Turtle; ATR